Визначення деяких параметрів регульованого електроприводу вібруючих робочих органів ґрунтообробних машин - Гаврилюк, Іван Антонович; Ільїчов, Іван Петрович; Хандола, Юрій Миколайович; Федюшко, Юрій Михайлович (Eastern-European Journal of Enterprise Technologies, 2010)
The Considered parameters controlled electric drive vibratory worker organ processing ground of the machines. It Is Installed that drive massive- rotors to engines enable, to account of the raised resistance of the rotor, reduce the pulsation of the current and moment, as a result this loss to energy in drive decrease